A novel method for 3D reconstruction: Division and merging of overlapping B-spline surfaces. (December 2016) - Yan, Rui-Jun; Wu, Jing; Lee, Ji Yeong; Khan, Abdul Manan; Han, Chang-Soo; Kayacan, Erdal; Chen, I-Ming
Abstract: B-spline surfaces, extracted from scanned sensor data, are usually required to represent objects in inspection, surveying technology, metrology and reverse engineering tasks. In order to express a large object with a satisfactory accuracy, multiple scans, which generally lead to overlapping patches, are always needed due to, inter-alia, practical limitations and accuracy of measurements, uncertainties in measurement devices, calibration problems as well as skills of the experimenter. In this paper, we propose an action sequence consisting of division and merging. While the former divides a B-spline surface into many patches with corresponding scanned data, the latter merges the scanned data and its overlapping B-spline surface patch. Firstly, all possible overlapping cases of two B-spline surfaces are enumerated and analyzed from a view of the locations of the projection points of four corners of one surface in the interior of its overlapping surface. Next, the general division and merging methods are developed to deal with all overlapping cases, and a simulated example is used to illustrate aforementioned detailed procedures. In the sequel, two scans obtained from a three-dimensional laser scanner are simulated to express a large house with B-spline surfaces. The simulation results show the efficiency and efficacy of the proposed method. In this whole process, storage space of data points is not increased with new obtained overlapping scans, and none of the overlapping points are discarded which increases the representation accuracy. We believe the proposed method has a number of potential applications in the representation and expression of large objects with three-dimensional laser scanner data. Highlights: A novel division and merging method of B-spline surface is proposed. All possible overlapping cases of two B-spline surfaces are enumerated. Scanned sensor data and its overlapping surface patch are merged as one B-spline surface. Storage space of data points is not increased with new obtained overlapping scans. Two 3D scans obtained from a simulated house are used to validate the proposed method.